150 Years of Blowing: Since John Hutchinson. Issue 5 (3rd October 1997) - Milic-Emili, Joseph; Marazzini, Luigi; D'Angelo, Edgardo
Abstract : Three recent advances in assessment of routine lung function are reviewed. In both normal subjects and patients with obstructive lung disease, the flows during the forced vital capacity (FVC) manoeuvre depend significantly on the pattern of the preceding inspiratory manoeuvre. Accordingly, the latter should be standardized in clinical and epidemiological studies. Although the nature of this phenomenon is not fully understood, stress relaxation of lung tissues probably plays the primary role. The negative expiratory pressure technique provides a simple and reliable tool for detecting expiratory flow limitation both at rest and during exercise. The method does not require body plethysmography or the patient's cooperation and coordination, and can be applied in any desired body posture. A simple method for monitoring FVC performance has been developed. It allows detection of flow limitation during the FVC manoeuvre.